Orthodontic Management of Class-I crowding in an adult male: A case report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
A 20 years old male presented with  Class-I malocclusion with crowding and lock bite on upper right and left lateral incisors. Treatment involved extraction of all first premolars. The alignment of teeth in both arches were achieved by edgewise orthodontic therapy.Ban J Orthod & Dentofac Orthop, October 2012; Vol-3, No.1